Foreign Language Acquisition Of Souvenir Seller In Bawomataluo Village - Saniago Dakhi (RETORIKA: Jurnal Ilmu Bahasa, 2016)
This research is carried by focusing on the description of the kinds and process of lexical items acquired by souvenir seller in Bawomataluo. To obtain the whole accurate data of these research questions, two instrument of data collection, interview and observation, were used. The result of data analysis are the eight English part of speech are acquired. It is discovered that lexical items acquired are dominated by noun. Verb and adjective posites at the next level of the amount of lexicals acquired. Adverb, conjunction, pronoun are less acquired. Interjection is more easily acquired by souvenir sellers. The processes involved to acquire the lexical consist of four are social, memory, compensation, and affective process. Key Word                 :    Foreign language acquisition, souvenir seller